A usability study for promoting eContent in higher education - Shiratuddin, Norshuhada; Hassan, Shahizan; Landoni, Monica (International Forum of Educational Technology & Society, 2003)

(untitled)
eContents used in education can be from a number of sources: from traditional electronic journals (eJournals), and electronic books (eBooks) to more specific formats such as: electronic research reports (eResearch-reports), electronic lecture modules (eLecture-modules), electronic lecture notes (eLecture-notes), and electronic lecture slides (eLecture-slides). This paper discusses a number of issues relevant to publishing of eContent. The first section describes the advantages, as well as the disadvantages of such contents. It also elaborates on how eContent can be promoted through the use of Internet, WWW and SMS. Next, related issues on the usability of eContent on the Web are discussed. Four popular usability design guidelines are studied and critically reviewed. The final part concludes that although designing and publishing eContent is more complex than the printed version, eContent has a huge potential in education.